The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1516-31802007000400004
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength in obese individuals and influence of upper-body fat distribution

Abstract: CONTEXT AND OBJECTIVE: Pulmonary dysfunction in obese individuals may be associated with respiratory muscle impairment, and may be influenced by predominance of upper-body fat distribution. The objective of this study was to evaluate the strength of respiratory muscles in obese individuals and to analyze the influence of adipose tissue distribution. DESIGN AND SETTING: Cross-sectional study on the preoperative period prior to bariatric surgery. Research developed within the Postgraduate General Surgery Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 35 publications
(65 reference statements)
4
53
1
12
Order By: Relevance
“…Magnani and Cataneo, 18 in a study only with obese individuals aged 20-64 years, verified that obesity does not impair RMS, since Pmax values did not achieve significance when compared with reference values for normality established by Neder et al. 12 Queiroz 25 conducted a study with obese and nonobese individuals (n = 100) separated by sex.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Magnani and Cataneo, 18 in a study only with obese individuals aged 20-64 years, verified that obesity does not impair RMS, since Pmax values did not achieve significance when compared with reference values for normality established by Neder et al. 12 Queiroz 25 conducted a study with obese and nonobese individuals (n = 100) separated by sex.…”
Section: Discussionmentioning
confidence: 83%
“…Our statistical analysis correlating WHR with RMS revealed no significant results, which are consistent with previous findings. 18,25 . Magnani and Cataneo 18 reported that obesity did not interfere with RMS at any age group and degree of obesity, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 However, no consensus has been reached in the literature concerning the behavior of the respiratory muscles in the presence of increased body mass index (BMI). [4][5][6] According to Magnani and Cataneo, 5 individuals with obesity have respiratory muscle dysfunction due to changes in the relationship between the lung, chest wall, and diaphragm muscle, which in turn alter respiratory mechanics and gas exchange. It is believed that these changes cause overload in the respiratory muscles, increasing the mechanical work involved in respiration.…”
Section: Introductionmentioning
confidence: 99%